Implementation of Merdeka Belajar at Kampus Merdeka"Rights to Learn Three Semesters Outside the Study Program" - Siti Romla (Proceedings of The ICECRS, 2021)
Merdeka Learning – Merdeka Campus is one of the policies of the Minister of Education and Culture, Nadiem Anwar Makariem. The policy aims to improve the competence of graduates, both soft skills and hard skills, to be more prepared and relevant to the needs of the times, to prepare graduates as future leaders of the nation with excellent and personality. One of the programs of the Merdeka Learning – Merdeka Campus policy is "The Right to Learn Three Semesters Outside the Study Program". Merdeka to study Independent campuses exist in order to prepare students to face social, cultural, work changes and rapid technological advances. The learning process in the Merdeka Campus is one of the most essential manifestations of student centered learning. Learning in the Merdeka Campus provides challenges and opportunities for the development of innovation, creativity, capacity, personality, and student needs, as well as developing independence in seeking and finding knowledge through realities and field dynamics such as ability requirements, real problems, social interaction, collaboration, self-management, performance demands, targets and achievements. With the concept of an independent campus, students are directed to be more ready to work, work together, be creative and be able to benefit themselves and other communities.